Olive oil tourism in Beira Interior Territory – the present offer - Pato, Maria Lúcia (2025)
This study aims to explore the potential of olive oil tourism as a key driver of rural development in the Beira Interior (BI) region and to assess the impact of its Protected Designation of Origin (PDO) olive oil. The research began with the mapping of all municipalities located within the BI olive oil PDO, using data from the Portuguese Direção Geral de Agricultura e Desenvolvimento Rural. In a second phase, an online search was conducted to identify assets relevant to the development of the olive oil tourism sector. The results reveal that, in the BI region, olive oil fairs and events, producer visits, olive farm tours, museums that allow visitors to experience traditional olive oil production and connect with rural culture, as well as rural accommodations, all contribute significantly to enriching the overall visitor experience. However, the gathered information highlights that the development and promotion of the three olive oil routes available in the region remain unsatisfactory. As for research limitations, this study was based exclusively on online searches. Its originality lies in the fact that research on olive oil tourism in Portugal is still at an early stage, and this study is among the first to explore the topic — to the best of the authors' knowledge, it is also the only study focusing specifically on the Beira Interior region, one of the six PDO-designated areas for olive oil production. Keywords: Olive oil tourism, Beira Interior PDO region, Endogenous Oil Resources, Portugal, Rural DevelopmentAcknowledgements: This work is funded by National Funds through the FCT - Foundation for Science and Technology, I.P., within the scope of the project Refª UIDB/00681/2020. Furthermore we would like to thank the CERNAS Research Centre and the Polytechnic Institute of Viseu for their support.DOI: https://doi.org/10.54663/2182-9306.2025.SpecialIssueMBP.101-117